2003
DOI: 10.1007/bf03347023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of licorice on the reduction of body fat mass in healthy subjects

Abstract: The history of licorice, as a medicinal plant, is very old and has been used in many societies throughout the millennia. The active principle, glycyrrhetinic acid, is responsible for sodium retention and hypertension, which is the most common side-effect. We show an effect of licorice in reducing body fat mass. We studied 15 normal-weight subjects (7 males, age 22-26 yr, and 8 females, age 21-26 yr), who consumed for 2 months 3.5 g a day of a commercial preparation of licorice. Body fat mass (BFM, expressed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…Aoki et al (2007) showed that LFO reduced body weight gain and abdominal white adipose tissues in mice fed high-fat diets. Furthermore, in other studies licorice hydrophobic flavonoids decreased abdominal fat in humans and mice (Armanini et al, 2003;Nakagawa et al, 2004). Plant herbs or their extracted oils containing terpenoids, may improve poultry health and production.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Aoki et al (2007) showed that LFO reduced body weight gain and abdominal white adipose tissues in mice fed high-fat diets. Furthermore, in other studies licorice hydrophobic flavonoids decreased abdominal fat in humans and mice (Armanini et al, 2003;Nakagawa et al, 2004). Plant herbs or their extracted oils containing terpenoids, may improve poultry health and production.…”
Section: Introductionmentioning
confidence: 84%
“…At day 49 birds fed the diets supplemented with licorice showed lighter (P <0.05) abdominal fat pads as compared to those fed the control diet (Table 5). Previous studies also showed that licorice flavonoids reduced the abdominal fat in other species (Armanini et al, 2003;Nakagawa et al, 2004;Tominaga et al, 2006;Aoki et al, 2007). Tominaga et al (2006) indicated that the effect of licorice on reduction of abdominal fat could be due to factors such as suppression in energy intake, reduction of lipid absorption, enhancement of fatty acid oxidation or reduction in biosynthesis of fatty acids.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The fall in both R/H and Xc/H values and the reduction in R/Xc ratio, suggested a fluid excess in the subcutaneous tissues (Piccoli et al, 1994(Piccoli et al, , 1995. In a previous study the bioelectrical impedance analysis demonstrated that liquorice at a dose of 3.5 g daily for 2 months significantly increased the body water (Armanini et al, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…There is conflicting information about the effectiveness of licorice for weight loss. 7,27 Licorice has antispasmodic, anti-inflammatory, laxative, and soothing properties. 7 The mineralocorticoid effects of licorice can induce fluid retention and worsen congestive heart failure.…”
Section: Figurementioning
confidence: 99%